Medical School Curricular Changes and Their Impact on Mental Health during the Onset of the COVID-19 Pandemic - Leen Al Kassab; Laila Fozouni; Christopher Reynolds; Phuong Pham; Valerie Dobiesz (Avicenna Journal of Medicine)
Objectives The main objectives were to identify and categorize the curricular changes that occurred in U.S. medical schools during the onset of the coronavirus disease 2019 (COVID-19) pandemic, and to identify the relationship between curricular changes and COVID-19 surges and student mental health.